Bridging the Gap: A 20-Year Experience with Vein Grafts for Free Flap Reconstruction. The Odds for Success. Issue 3 (September 2018) - Inbal, Amir; Silva, Amanda K.; Humphries, Laura S.; Teven, Chad M.; Gottlieb, Lawrence J.
Abstract : Background: Successful free tissue transfer requires tension-free microvascular anastomosis. Vein grafts are used when this cannot be obtained, which increases microsurgical complexity and the chance of vessel thrombosis. Previous studies on vein grafts are limited to low numbers and selected techniques, making it difficult to draw conclusions. Methods: A retrospective chart review was performed for all patients who underwent vein grafts in free flap reconstruction from 1995 to 2015. Information on patient and flap characteristics, returns to the operating room, and flap loss was analyzed. Results: Seventy-two free flap reconstructions requiring 122 vein grafts were performed in the genitourinary/perineal (49 percent) and head and neck (38 percent) regions. The majority were performed in the initial operation (82 percent) and, of those, the majority were planned (71 percent). The most common vein graft types used were transposition arteriovenous loops (57 percent) and interpositions (26 percent). Of the initial cases, 22 percent returned to the operating room, resulting in a 7 percent total flap loss rate and a 7 percent partial flap loss rate. On univariate analysis, graft timing/planning, gap type, vein graft type, and reconstruction location were significantly associated with take-backs and flap loss. However, gap type and location seem to be strongly associated with graft timing/planning and vein graft type. Graft type and planning/timing do not have as strong a relationship and seem to independently relate to flap loss. Conclusions: Vein grafts are more successful when planned and when performing transpositions and arteriovenous loops over interpositions. These graft types should be considered over interpositions when possible. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.